A unified modeling of muti-sources cyber-attacks with uncertainties for CPS security control. Issue 1 (January 2021) - Ge, Hui; Yue, Dong; Xie, Xiangpeng; Deng, Song; Dou, Chunxia
Highlights: In this paper, double closed-loop framework is proposed with the functions of faults and cyber-attacks detection. The models of cyber-attacks, denial-of-service, information disclosure (privacy attack), stealthy attack and replay attacks, are formulated to be typical NCS models with parameter uncertainties from control theory perspective. Information technique (IT) is synthesized together with control theory, and a novel framework is designed based on typical CPS structure, effective attack defense scenarios is devised and applied on this framework to detect and identify the cyber-attacks. Abstract: In this paper, the issue of CPS security is investigated. By analyzing the process of multi-sources cyber-attacks of denial-of-service (DoS), information disclosure, stealthy attack and replay attack, a unified system model with uncertainties is formulated. Under this system model framework, robust control theory is applied to design the control scenarios for cyber-attack prevention. Furthermore, a double closed-loop NCS framework combined with information integration technology is proposed, necessary conditions for security guarantee are derived. Finally, a DC motor speed moderating example is given to demonstrate the problem.